Phylogeny of thrips (Insecta: Thysanoptera) based on five molecular loci. (25th September 2012) - BUCKMAN, REBECCA S.; MOUND, LAURENCE A.; WHITING, MICHAEL F.
Abstract : The order Thysanoptera (Paraneoptera), commonly known as thrips, displays a wide range of behaviours, and includes several pest species. The classification and suggested relationships among these insects remain morphologically based, and have never been evaluated formally with a comprehensive molecular phylogenetic analysis. We tested the monophyly of the suborders, included families and the recognized subfamilies, and investigated their relationships. Phylogenies were reconstructed based upon 5299 bp from five genetic loci: 18S ribosomal DNA, 28S ribosomal DNA, Histone 3, Tubulin‐alpha I and cytochrome oxidase c subunit I. Ninety‐nine thrips species from seven of the nine families, all six subfamilies and 70 genera were sequenced. Maximum parsimony, maximum likelihood and Bayesian analyses all strongly support a monophyletic Tubulifera and Terebrantia. The families Phlaeothripidae, Aeolothripidae, Melanthripidae and Thripidae are recovered as monophyletic. The relationship of Aeolothripidae and Merothripidae to the rest of Terebrantia is equivocal. Molecular data support previous suggestions that Aeolothripidae or Merothripidae could be a sister to the rest of Terebrantia. Four of the six subfamilies are recovered as monophyletic. The two largest subfamilies, Phlaeothripinae and Thripinae, are paraphyletic and require further study to understand their internal relationships.